Model Study of Information Dissemination in Microblog Community Networks - Bo Wang; Jianhua Zhang; Haifeng Guo; Yuwang Zhang; Xiaotuo Qiao (Discrete Dynamics in Nature and Society)
We build an information dissemination model based on SIR model to study information dissemination in microblog networks. We consider different influence factors of information dissemination such as activity, credibility, and weight of network and construct calculation methods of various parameters, for instance, direct immune rate, indirect immune rate, and information dissemination rate. Meanwhile, by collecting data from API in Weibo and using the result of microblog information dissemination life cycle analysis, we utilize the model to conduct simulation and get the change trend of proportion in Stages S, I, and R. After comparing with the actual situation, this model is proved to be effective in predicting the trend of information dissemination.